Productivity and Performance of Malaysian Food Manufacturing Industry - Ahmed, Elsadig Musa (1998)
Although the productivity growth and performance of the food manufacturing industry has improved in the recent years, the industry is still behind the other manufacturing industries, specifically the non-resource based industry such as the electronics and electrical industries after the structural transformation took place in Malaysian economy in 1987. The manufacturing industry sector becomes as an engine of growth instead of the agricultural sector. There is imbalance growth between the food manufacturing industry and the other manufacturing industries, in terms of its contribution to the output growth, value added, employment generation, exports, imports and the investment opportunities. The analysis of the food manufacturing sector showed a characteristic low productivity and inefficiency problem through analysis of the food manufacturing sector. In this study autoregression estimator was employed to estimate the sources of productivity growth in 28 food manufacturing industries in Malaysia for the time series data from 1 970-1 993 obtained from the department of statistics. Two models were generated from the production function. The first model is the decomposition of the output growth into the contribution of capital, increased usage of labour, material and total factor productivity growth. On the other hand, the second model is the decomposition of the labour productivity growth (output per worker) into the capital deepening (capital per worker), increasing usage of the material-labour ratio (material per worker) and total factor productivity growth. The study found that the output growth is contributing more than the labour productivity growth to the food manufacturing industry productivity in terms of the annual average growth rate of the food manufacturing industries. The contribution of the two indictors to the food manufacturing industry growth as the output of the two models during the study period were 11% and 1.8% respectively. The highest contribution in terms of annual average growth rate, of the output growth to the food manufacturing industry productivity growth was the contribution of total factor productivity growth (17%). For labour productivity growth, the highest contribution was the contribution of capital deepening (9.6%). The major sources of productivity growth of two indicators of the individual industries, are the spices and curry powder contributed 53% to labour productivity growth of overall food industries. The major source of productivity growth of output growth was the contribution of pineapple canning (23%).